Valproate Reduces Delayed Brain Injury in a Rat Model of Subarachnoid Hemorrhage. Issue 2 (February 2017) - Hamming, Arend M.; van der Toorn, Annette; Rudrapatna, Umesh S.; Ma, Lisha; van Os, Hine J.A.; Ferrari, Michel D.; van den Maagdenberg, Arn M.J.M.; van Zwet, Erik; Poinsatte, Katherine; Stowe, Ann M.; Dijkhuizen, Rick M.; Wermer, Marieke J.H.
Abstract : Background and Purpose—: Spreading depolarizations (SDs) may contribute to delayed cerebral ischemia after subarachnoid hemorrhage (SAH). We tested whether SD-inhibitor valproate reduces brain injury in an SAH rat model with and without experimental SD induction. Methods—: Rats were randomized in a 2×2 design and pretreated with valproate (200 mg/kg) or vehicle for 4 weeks. SAH was induced by endovascular puncture of the right internal carotid bifurcation. One day post-SAH, brain tissue damage was measured with T2 -weighted magnetic resonance imaging, followed by cortical application of 1 mol/L KCl (to induce SDs) or NaCl (no SDs). Magnetic resonance imaging was repeated on day 3 followed by histology to confirm neuronal death. Neurological function was measured with an inclined slope test. Results—: In the groups with KCl application, lesion growth between days 1 and 3 was 57±73 mm3 in the valproate-treated versus 237±232 mm3 in the vehicle-treated group. In the groups without SD induction, lesion growth in the valproate- and vehicle-treated groups was 8±20 mm3 versus 27±52 mm3. On fitting a 2-way analysis of variance model, we found a significant interaction effect between treatment and KCl/NaCl application of 161 mm3 ( P =0.04). Number and duration of SDs, mortality, and neurological function were not statistically significantly different between groups. Lesion growth on magnetic resonance imaging correlated to histological infarct volume (Spearman's rho =0.83; P =0.0004), with areas of lesion growth exhibiting reduced neuronal death compared with primary lesions. Conclusions—: In our rat SAH model, valproate treatment significantly reduced brain lesion growth after KCl application. Future studies are needed to confirm that this protective effect is based on SD inhibition. Abstract : Supplemental Digital Content is available in the text.